Stable Isotope Analysis of Northern Pintail (Anas acuta) Feathers Wintering on Junam Reservoir - Jeong, Kahee; Bae, In-Ae; Kim, Jong-Yun; Song, Kyuseok; Lee, Si-Wan; Kang, Tae-Han (Asian Journal of Chemistry, 2014)
For the first time in Korea, stable isotope ratio mass spectroscopic analysis method was introduced as an alternative method to track the movement of the migratory birds. Hydrogen isotope ratio (d2H) and oxygen isotope ratio (d18O) of the feather samples were collected from northern pintail, which were captured in Junam Wetland Park and were measured using a continuous flow-isotope ratio mass spectrometer. The d2H values of all feathers show a bimodal frequency distribution with a wide range of d2H values (-30 ‰ to -120 ‰), while the range of d18O values was relatively very small (ca. 6-18 ‰). The difference between the two modes in the frequency distribution of d2H values for male was more than that for female. Although the two-dimensional plot of d2H versus d18O can provide the information on the breeding ground of the migratory wild birds. The northern pintails captured in Junam Wetland Park have more than two geographical origins.